The relationship between test preparation and state test performance: Evidence from the Measure of Effective Teaching (MET) project - Hongli Li; Yao Xiong (Arizona State University, 2018)
The passage of the NCLB Act enhanced accountability policies in the United States, and standardized testing became prevalent as a policy tool to ensure accountability in K-12 education. Given the high stakes of state administered accountability tests, more school teachers have adopted test-preparation strategies to ensure satisfactory student performance on state tests. However, it remains unclear as to whether and how test preparation relates to students' state test performance. In this study, by drawing on the Measure of Effective Teaching (MET) longitudinal dataset, we examined the relationship between test preparation and students' state test performance. We found that students with lower test performance in Year 1 received more test preparation in Year 2; however, the effects of test preparation on students' state test performance were rather small and mixed. In regard to racial differences, we found that Black and Hispanic students received more test preparation than White students. Further, the effect of test preparation measured by the item "practicing for the state test" on state test performance was significantly greater for Black and Hispanic students than for White students. The implications of the study, its limitations, and directions for future research are also discussed.